Сучасні читацькі уподобання та збагачення словникового складу англійської мови - Головко, Олександра Миколаївна; Golovko, O. M. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Статтю присвячено дослідженню інноваційних номінацій, що розкривають особливості читацьких смаків, які не могли не зазнати змін у високорозвинених англомовних суспільствах. Динамічний розвиток англійської мови дає змогу їй задовольнити потреби вербалізації новітнього лакунарного явища. Аналізовані неологізми позначають нові жанри літератури, вони пов’язані з назвами найпопулярніших книг, що залучаються для розкриття елементів буття сучасної людини. Книги поступово переміщуються до віртуальної площини, що викликає і потребу мовної ідентифікації цифрових примірників, і вибір лінгвальних форм репрезентації стандартних паперових видань. The article analyses the innovative linguistic instantiations of the readers’ tastes which cannot have avoided undergoing some changes in highly developed English-speaking societies. Dynamic development of the English language allows satisfying its needs of representing novel previously lacunar phenomena. The analyzed neologisms identify new genres of literature, some of them incorporate titles of the well-known books which are intentionally used to represent the elements of contemporary living connected with modern reading habits. Books gradually move to the digital plane which requires the means of linguistic representation of both digital and standard paper editions. This process is characterized by polynomination which can be explained by the fact of the computer lexicon being young and relatively unstable. The research identified the dominating wordbuilding patterns that the language resorted to when coining new words.
Modern Reading Habits and the Enrichment of English Vocabulary
Keywords: інновація; innovation; вербалізація; instantiation